Mysticism and Mind: A Critical Review of Parapsychological Studies in India - Udayveer Singh Wilkhu; Sangeeta Kakkar (International Journal of Education Sciences, 2025)
Parapsychology holds a unique place in India, shaped by the country’s rich spiritual traditions and deep-rooted mysticism. The review aimed to look at how the field has evolved in India, blending with cultural beliefs and being subject to scientific scrutiny. It highlights the connection between ancient spiritual practices like meditation, yoga, and the third eye, and modern research into phenomena like extrasensory perception (ESP), telepathy, and psychokinesis. This review paper integrated the previous 10 years' databases from Web of Science, Scopus, SpringerLink, and Google Scholar. Result: While Western academia tends to be more skeptical about parapsychology, Indian researchers have been more open, combining spiritual knowledge with scientific methods to explore these unusual experiences. The review takes a close look at studies on telepathy, healing, and near-death experiences, acknowledging both the promise and limitations of current research approaches. The paper discusses a balanced approach that integrates both traditional wisdom and modern science to deepen our understanding of consciousness and paranormal experiences. It also discusses the challenges faced by parapsychology in India, such as the difficulty of gaining widespread academic acceptance and the lack of standardized measures. The review suggests that using research methods tailored to Indian culture could improve the credibility and recognition of the field. It concludes by noting that India has the potential to become a leader in global parapsychological research by drawing on its cultural strengths and growing scientific expertise.
Keywords: Indian mysticism; consciousness; extrasensory; parapsychology; spiritual traditions